Climate Change and Emerging Infectious Diseases: A Precarious Relationship. - Munro, Nancy (AACN Advanced Critical Care)
Climate change is apparent. Temperatures are rising. Floods are more frequent and devastating. Climate changes can favor the development of emerging infectious diseases. The number of animal reservoirs and vector hosts can increase, further spreading pathogens. Many emerging infectious diseases were not historically considered major threats in US but have become a major concern in US territories and various states. In June 2024, the Centers for Disease Control and Prevention issued a Health Alert Network advisory about an increase in local transmission of dengue fever. Preventing the transmission of emerging infectious diseases has become a focus of regulatory agencies. Nurse education at all levels should include infectious diseases and be coordinated with local, state, and regional institutions. Emerging infectious diseases are now formidable challenges to health care.